Applied performance analysis practices in women's football - Harkness-Armstrong, A.; Seth, L.; Lowry, R.; Datson, N. (International Journal of Sports Science and Coaching, 2025)
The aim of this study was to investigate the applied performance analysis (PA) practices within women's football. An online survey was developed to assess PA practices (team, individual and opposition match analysis, training analysis, coach behaviour analysis, best practice analysis, talent identification and recruitment, and game insights), use of technology, and considerations for PA practices within women's football. Thirty-nine participants (female n = 13; male n = 26) responsible for delivering PA within women's football completed the online survey between January and August 2023. Participants worked across different competitive levels of women's football (international n = 11; senior domestic top tier n = 12; senior domestic second tier n = 7, senior domestic third tier and below n = 9; youth (<U23) domestic n = 10), including seven participants who worked across multiple levels of competition. Participants predominantly conducted team (100%), individual (79%) and opposition (84%) match analysis, and training analysis (74%). Data collection and analysis, feedback mechanisms, and application of insights gained from PA practices typically varied across competitive standards. A wide variety of software were reported for data collection (e.g. HUDL, Veo), storing and managing data and/or video (e.g. HUDL, Veo), conducting statistical analysis (e.g. Microsoft Excel, R), and providing feedback (e.g. Microsoft PowerPoint, HUDL) across competitive standards. Thirty-one respondents identified specific considerations or challenges faced when implementing PA (e.g. limited resources (42%), data availability (19%), facilities (19%)). The findings of this survey can be used to inform and develop applied PA practices in women's football, education, and development opportunities for current and aspiring performance analysts.